Private Market Financing for Developing Countries. (World Economic and Financial Surveys; World Economic and Financial Surveys ;, 1995)
This study surveys recent trends in private market financing for developing countries. In addition to examining developments in flows to developing countries through banking and securites markets, it analyzes the institutional and regulatory framework for developing country finance, institutional investor behavior and pricing of developing country stocks, management of public sector debt and implications of private external borrowing for macroeconomic policy management, and progress in commercial bank debt restructuring in low-income countries.